Strategi Pengelolaan Keuangan Keluarga Berpenghasilan Tidak Tetap dalam Menghadapi Financial Stress di Kecamatan Lamba Leda Selatan - Maria Yolantia Sajung; Petrus E. de Rozari; Efandri Agustian; Wehelmina M. Ndoen (Fakultas Hukum dan Ekonomi Bisnis, 2026)
This study aims to describe the level of financial stress and financial management strategies employed by families with irregular incomes in Bangka Pau Village, South Lamba Leda District. A mixed-methods approach was used, collecting quantitative data through questionnaires and qualitative data through in-depth interviews. The results indicate that families' financial stress levels are high, primarily due to seasonal income uncertainty, fluctuations in the prices of basic necessities, and significant social and customary obligations. Facing these challenges, families employ simple financial management strategies, such as planning daily expenses, cutting non-priority expenses, and prioritizing basic needs and education costs. Furthermore, families rely on secondary income and social support through customary mechanisms such as arisan (social gatherings) and assistance from relatives. These findings suggest that families' financial adaptation strategies focus more on short-term sustainability and fulfilling customary obligations that cannot be postponed.